SISTEM PENDUKUNG KEPUTUSAN PENERIMA DISPENSASI UKT(UANG KULIAH TUNGGAL) DI FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM UNIVERSITAS SEBELAS MARET SURAKARTA DENGAN AHP ( ANALYTICAL HIERARCHY PROCESS) - Falentina, Fora; Fitriasih, Sri Hariyati; Irawati, Tri (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2025)
Research Report entitled "Decision Support System for Determining Recipients of UKT Dispensation (Single Tuition Fee) at the Faculty of Mathematics and Natural Sciences UNS with the AHP Method" aims to facilitate the Leaders who will provide UKT relief Dispensation for students who apply for UKT relief Dispensation for applications paid each semester. The many criteria that affect the weight of the score determining the recipient of UKT relief dispensation make it difficult to calculate the amount of weight that has been submitted and the accuracy in determining the weight of the score for each criterion cannot be ascertained, so the Decision Support System with the AHP method is the right method to overcome the problem of determining recipients of UKT dispensation with many supporting criteria submitted. These criteria include UKT Costs, Parental Income, Working Parents, Completeness of Parents, Number of Family Dependents, Number of children in the family, Child No., Status of Siblings applying and education, Ownership status, Electricity Costs/month and Number of Vehicles owned